Cardiac mitochondrial damage and biogenesis in a chronic model of type 1 diabetes - Xia Shen (2018)
Diabetic cardiomyopathy is a common complication leading to heightened risk of heart failure and death. In the present report, we performed proteomic analysis on total cardiac proteins from the OVE26 mouse model of type 1 diabetes to identify protein changes that may contribute to diabetic cardiomyopathy. This analysis revealed that a surprising high proportion (12 of 20) of the altered proteins that could be identified by mass spectrometry were of mitochondrial origin. All but one of these proteins were upregulated by diabetes. Quantitative RT-PCR, performed for two of these proteins, indicated that part of the upregulation was attributed to increased messenger RNA levels. Morphological study of diabetic hearts showed significantly increased mitochondrial area and number as well as focal regions with severe damage to mitochondria. Diabetic mitochondria also showed reduced respiratory control ratio (9.63 ± 0.20 vs. 6.13 ± 0.41, P < 0.0001), apparently due to reduced state 3 rate, and diminished GSH level (5.5 ± 0.9 vs. 8.2 ± 2.5 μmol/mg protein, P α 0.05), indicating impaired mitochondrial function and increased oxidative stress. Further examination revealed increased mitochondrial DNA (1.03 ± 0.18 vs. 0.69 ± 0.13 relative copy number, P α 0.001) and a tendency to higher protein yield in OVE26 cardiac mitochondria, as well as increased mRNA level for mitochondrial transcription factor A and two mitochondrial encoded proteins. Taken together, these results show that mitochondria are a primary target in the diabetic heart, probably due to oxidative stress, and that this damage coincides with and may stimulate mitochondrial biogenesis.